Kajian Pengembangan Industri Pangan Kreatif Berbahan Baku Kelapa Di Kabupaten Minahasa Selatan - Koapaha, Teltje; Pinatik, Herry F.; Langi, Tineke M.; Tooy, Dedie (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2019)
Agricultural development over the past decade, is more identical to commodity development, which focuses on meeting domestic food needs. The development of globalization, a country in this case the government, must be able to facilitate and encourage the community to develop productive activities, including developing the creative food industry, which is characterized not only by fulfilling quantity, quality, but having selling value, or the value of excellence product specifics (preposition value), and provide economic (added value). The synergy of various parties (stake holders) encourages increased production of creative food products by intensifying : technology, information, ideas and creativity as well as skills that emerge from the community, both individual farmers and industrial groups in the South Minahasa Regency. The objectives of this study are: 1. Identify the types and characteristics of coconut-based food industries in South Minahasa regency and 2. Calculate the economic added value of the development of coconut-based food industries in South Minahasa regency. 3. Obtain appropriate methods, strategies and models for the development of a food industry based on coconut in South Minahasa Regency. This study uses several methods, namely: descriptive method, calculation of added value according to Coster and Schaffer, 1982) and the SWOT method for obtaining methods, strategies and models for the development of creative food industries that are suitable in South Minahasa regency. The results showed that there were 3 types of development of creative food industries made from coconut which already existed in South Minahasa Regency, namely: 1. culinary, 2. medicines 4. research development. From this type of creative food industry, it has provided real economic added value for farmers, industrial groups and macro for the economic growth of the community, when applying methods, strategies and models that match the potential and characteristics in South Minahasa Regency. Keywords: development, creative food industry, coconut raw materials